Forschungen an alten Arten. 214. Beitrag zur Kenntnis der Hispinae (Coleoptera: Chrysomelidae). - Uhmann, Erich Leo Ludwig (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The author being unable to study the four species dealt with in this paper when he was preparing the manuscript for the "Coleopterorum Catalogus, 1957-1958, Hispinae" has to thank his friend, J. Demaux, Caen, who searched for these species in the Paris Museum. The type of Hispa longespinosa Fairm. could be found, Hispa incerta Chap. was new arranged, Cephaloleia microdonta Fairm. remains dubious, and Uroplata trivittata Chap. is described as new.